Practices Of Local Democracy And Power Sharing In The Indigenous Community Of Kampung Kuta - Wiwi Widiastuti; Taufik Nurohman; Fitriyani Yuliawati; Kamarul Zaman Haji Yusoff (Universitas Muhammadiyah Ponorogo, 2026)
This paper aims to explain local democracy in indigenous communities. To understand how local democracy is practiced in indigenous communities, it is necessary to trace how power is distributed in these communities. This study uses qualitative research methods that allow for in-depth exploration of local democracy and power distribution in the Kuta indigenous community. The practice of democracy in indigenous communities is not only present in formal mechanisms regulated by the state, but also through informal mechanisms rooted in tradition and local wisdom. In indigenous communities, regulations in various aspects of life are not only part of the functioning of formal government but also become a realm of regulation based on local customary values. Meanwhile, the democratic values of indigenous Indonesian communities generally stem from a spirit of togetherness and kinship. The tradition of deliberating to resolve issues, followed by consensus-based decision-making, is a manifestation of these values of togetherness and kinship. An important finding of this study is that the formal power structure in Kampung Kuta is divided into two structures, namely the formal structure run by the village government and the informal structure run by the customary leader, which includes the kuncen, customary elders, and village elders. The results of the study show that the practice of local democracy in Kampung Kuta can balance the division of formal and informal power, which serves to maintain community identity, strengthen social life, and ensure the sustainability of cultural values. This confirms how local democracy can adapt to traditional values.